Catalyst having a catalyst metal supported on a hexagonal crystal structure support and method for producing the same

By using hexagonal boron nitride as a support body and loading catalyst metal, the problem of inadequate dispersion of existing catalysts and unstable under industrial conditions is solved, and high -active and stable catalysts are achieved. Essence

CN115066295BActive Publication Date: 2025-01-28KOREA INST OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180011766.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-07
Filing Date
2021-02-02
Publication Date
2025-01-28
Estimated Expiration
2041-02-02

AI Technical Summary

Technical Problem

The existing catalysts are insufficiently dispersed on the support, have low catalytic activity, and are prone to methanation when using a support made of carbon under industrial conditions, resulting in unstability of the catalyst.

Method used

The single crystal substance containing the hexagonal structure is used, such as the hexagonal crystal boron nitride as the support body, and the metal metal metal on its upper load, such as 钌, regulates the shape and size of the metal metal by thermal treatment to improve the catalytic activity and stability.

Benefits of technology

The uniform dispersing of the catalyst metal on the support body, improving the catalytic activity and conversion frequency, avoiding methane problems, and ensuring the stability and efficiency of catalysts under industrial conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115066295B_ABST
    Figure CN115066295B_ABST
Patent Text Reader

Abstract

The present invention relates to a catalyst in which a catalyst metal is supported on a support body including a single crystal substance having a hexagonal crystal structure, and a method for producing the same, wherein the catalyst can be effectively used for an ammonia dehydrogenation reaction or an ammonia synthesis reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst in which a catalyst metal is supported on a support body including a single crystal substance having a hexagonal crystal structure, and a method for producing the same, wherein the catalyst can be effectively used for an ammonia dehydrogenation reaction or an ammonia synthesis reaction. Background Art

[0002] Due to the depletion of fossil energy and environmental pollution problems, there is a great demand for new renewable alternative energy that can replace fossil fuels, and hydrogen has attracted attention as one of such alternative energy sources.

[0003] Fuel cells and hydrogen combustion devices use hydrogen as a reaction gas. In order to apply fuel cells and hydrogen combustion devices to, for example, automobiles and various electronic products, a stable and continuous supply and storage technology of hydrogen is required.

[0004] In order to supply hydrogen to the hydrogen utilization device, a method of supplying hydrogen from a separately provided hydrogen supply point each time hydrogen is needed can be adopted. In this method, compressed hydrogen or liquid hydrogen can be used to store hydrogen.

[0005] Alternatively, a method may be adopted in which a substance that stores and generates hydrogen is placed on a hydrogen utilization device, hydrogen is generated by the reaction of the substance, and the hydrogen is supplied to the hydrogen utilization device. Examples of such methods include methods using metal hydrides, methods using adsorption, desorption / carbon, and chemical methods (chemical hydrogen storage).

[0006] As such a hydrogen-generating substance, for example, ammonia borane, ammonia, etc. can be used, and a catalyst is used in the process of dehydrogenating these substances.

[0007] Among them, ammonia has a high hydrogen storage density (about 17.7 wt %) and is easy to synthesize.

[0008] For reference, the ammonia dehydrogenation reaction and the ammonia synthesis reaction are shown in the following reaction formula 1.

[0009] [Reaction 1]

[0010]

[0011] Conventionally, catalytic metals supported on supports have been studied as catalysts for ammonia dehydrogenation reactions and ammonia synthesis reactions. However, there is room for improvement, such as insufficient dispersion of the catalytic metals in the supports and low catalytic activity.

[0012] Furthermore, a serious disadvantage of using a support made of carbon is its sensitivity to added hydrogen under industrial conditions. Specifically, the support made of carbon gradually transforms into methane, resulting in the gradual disappearance of the support and causing difficulties in operation. Summary of the invention

[0013] Technical issues to be solved by the invention

[0014] An object of the present invention is to provide a catalyst for ammonia dehydrogenation or ammonia synthesis having excellent catalytic activity.

[0015] An object of the present invention is to provide a catalyst which is stable and does not decompose in an ammonia dehydrogenation reaction or an ammonia synthesis reaction.

[0016] The object of the present invention is not limited to the above-mentioned object. The object of the present invention will become more clear through the following description, and is achieved through the solutions and combinations described in the claims.

[0017] Means for solving technical problems

[0018] A catalyst according to an embodiment of the present invention may include a support including a single crystal material having a hexagonal crystal structure and a catalyst metal supported on the support.

[0019] The single crystal material may include one or more selected from the group consisting of hexagonal boron nitride (h-BN), boron nitride nanotubes (BNNTs), boron nitride nanoribbons (BNNRs), boron nitride nanosheets (Boron nitride nanosheets), carbon nanotubes (CNTs), carbon nanofibers (CNFs), reduced graphene oxide (rGO) and silicene.

[0020] The catalyst metal may include one or more selected from the group consisting of ruthenium (Ru), nickel (Ni), rhodium (Rh), iridium (Ir), cobalt (Co), iron (Fe), platinum (Pt), chromium (Cr), palladium (Pd) and copper (Cu).

[0021] The catalyst metal may be supported in an amount of 0.01 wt % to 3 wt % based on the total weight of the catalyst.

[0022] The catalyst metal may include rod-shaped particles. The rod-shaped particles may have a length of 10 nm to 80 nm and an aspect ratio of 1.2 to 20.

[0023] The catalyst metal includes at least one particle selected from the group consisting of hexagonal particles, spherical particles, and semi-sphere particles. The diameter of the particles may be 2 nm to 40 nm.

[0024] The TOF (Turnover frequency) of the catalyst reaction can be 7,500 h -1 above.

[0025] The catalyst can be used for an ammonia dehydrogenation reaction or an ammonia synthesis reaction.

[0026] According to one embodiment of the present invention, a method for manufacturing a catalyst may include the following steps: a step of impregnating a catalyst metal precursor solution into a support body comprising hexagonal boron nitride; a step of drying the impregnated resultant; and a step of heat-treating the dried resultant to obtain a catalyst having the catalyst metal loaded on the support body.

[0027] In the manufacturing method, the dried resultant may be heat-treated at 200°C to 700°C.

[0028] In the manufacturing method, the dried resultant may be heat-treated in an air environment to form the catalyst metal into rod-shaped particles.

[0029] In the production method, the dried product may be heat treated in an inert gas environment or a vacuum environment to form the catalyst metal into particles having any one or more shapes selected from the group consisting of hexagonal, spherical, and semi-sphere shapes.

[0030] In the manufacturing method, the dried product may be heat-treated in an inert gas environment or a vacuum environment to epitaxially grow the catalyst metal.

[0031] Effects of the Invention

[0032] The catalyst according to the present invention uses hexagonal boron nitride having a large specific surface area as a support, and the catalyst metal is uniformly supported therein, so that the catalyst activity is excellent.

[0033] The catalyst according to the present invention uses hexagonal boron nitride, which is stable and does not decompose under industrial conditions of ammonia dehydrogenation reaction or ammonia synthesis reaction, as a support, and thus does not cause methanogenesis problems and stably maintains catalytic activity.

[0034] The method for producing a catalyst according to the present invention can adjust the morphology and / or size of a catalyst metal by performing a heat treatment under specific conditions, and can obtain a catalyst having a high active site.

[0035] The catalyst according to the present invention has high catalytic activity and high turnover frequency, and therefore can exhibit the same or improved performance as before even in a small amount.

[0036] Compared with conventionally known catalysts, the catalyst according to the present invention has a much better conversion frequency for ammonia conversion reaction, and thus can significantly improve hydrogen production efficiency.

[0037] The effects of the present invention are not limited to the effects mentioned above. It should be understood that the effects of the present invention include all the effects that can be inferred in the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the XRD analysis result of the catalyst according to Example 1 of the present invention.

[0039] Figure 2 These are the results of measuring the ammonia conversion rates of the catalysts of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 of the present invention.

[0040] Figure 3a is the result of γEM analysis of the catalyst of Example 1 according to the present invention. Figure 3b This is the TEM analysis result of the catalyst of Example 2 according to the present invention. Figure 3c This is the TEM analysis result of the catalyst of Example 3 according to the present invention. DETAILED DESCRIPTION

[0041] The above objects, other objects, features and advantages of the present invention are easily understood through the following preferred embodiments related to the accompanying drawings. However, the present invention is not limited to the embodiments described herein, but can be specifically implemented in other ways. On the contrary, the embodiments introduced herein are provided to make the disclosed contents thorough and complete, and to fully convey the ideas of the present invention to ordinary technicians in the technical field of the present invention.

[0042] Each of the accompanying drawings is described, and similar reference symbols are used for similar structural elements. In the accompanying drawings, for the clarity of the present invention, the size of the structure is enlarged than the actual size. Terms such as the first and the second can be used to describe various structural elements, but the structural elements should not be limited by the terms. The terms are used only for the purpose of distinguishing one structural element from other structural elements. For example, without departing from the scope of the present invention, the first structural element can be named as the second structural element, and similarly, the second structural element can also be named as the first structural element. Unless clearly indicated differently in the context, the expression in the singular includes the expression in the plural.

[0043] It should be understood that in this specification, the terms "including" or "having" are used to specify the existence of features, numbers, steps, actions, structural elements, components or combinations thereof recorded in the specification, but do not exclude in advance the existence or additional possibility of one or more other features or numbers, steps, actions, structural elements, components or combinations thereof. Moreover, when it is mentioned that a layer, film, region, plate or other part is "above" another part, this includes not only the case where it is "directly" "above" another part, but also the case where another part is sandwiched therebetween. On the contrary, when it is mentioned that a layer, film, region, plate or other part is "below" another part, this includes not only the case where it is "directly" "below" another part, but also the case where another part is sandwiched therebetween.

[0044] Unless otherwise expressly stated, all numbers, values ​​and / or expressions representing the amounts of ingredients, reaction conditions, polymer compositions and blends used in this specification are approximate values, which reflect the various uncertainties of the measurements resulting from obtaining these values ​​from essentially different things, and should therefore be understood to be modified by the term "about" in all cases. In addition, in the case of numerical ranges disclosed in this description, these ranges are continuous, unless otherwise stated, and cover all values ​​from the minimum value of these ranges to the maximum value including the maximum value. Furthermore, in the case where these ranges refer to integers, unless otherwise stated, all integers from the minimum value to the maximum value including the maximum value are covered.

[0045] The catalyst according to the present invention includes a support body including a single crystal substance having a hexagonal crystal structure and a catalyst metal supported on the support body.

[0046] The single crystal material of the hexagonal crystal structure may include one or more selected from the group consisting of hexagonal boron nitride (h-BN), boron nitride nanotubes (BNNTs), boron nitride nanoribbons (BNNRs), boron nitride nanosheets (Boron nitride nanosheets), carbon nanotubes (CNTs), carbon nanofibers (CNFs), reduced graphene oxide (rGO) and silicene.

[0047] More specifically, the hexagonal single crystal material may have a two-dimensional plate structure. For example, the hexagonal single crystal material may include hexagonal boron nitride, boron nitride nanobelts, boron nitride nanosheets, reduced graphene oxide, silicene, and preferably hexagonal boron nitride.

[0048] Two-dimensional materials have been studied a lot recently due to their new physical and chemical properties that have not been found in existing bulk materials. Hexagonal boron nitride has the same hexagonal shape as graphene, but is composed of boron and nitrogen instead of carbon, and is also called "white graphene". Hexagonal boron nitride has no dangling bonds on the surface and is very flat, so it can be effectively used as a support for catalyst metals.

[0049] The hexagonal single crystal material has a large surface area, so the catalyst metal can be evenly dispersed thereon, thereby greatly improving the catalytic activity. For example, the surface area of ​​the hexagonal boron nitride can be 2m 2 / g to 50m 2 / g.

[0050] The hexagonal boron nitride can play the role of a thermodynamically stable support. Therefore, it can maintain its shape, characteristics, etc. without methanation or decomposition under industrial conditions of ammonia dehydrogenation reaction or ammonia synthesis reaction. Therefore, the catalyst can stably maintain catalytic activity.

[0051] The catalyst metal may include one or more selected from the group consisting of ruthenium (Ru), nickel (Ni), rhodium (Rh), iridium (Ir), cobalt (Co), iron (Fe), platinum (Pt), chromium (Cr), palladium (Pd) and copper (Cu). Specifically, when the catalyst is used for ammonia dehydrogenation reaction, the catalyst metal may include ruthenium (Ru). On the other hand, when the catalyst is used for ammonia synthesis reaction, the catalyst metal may further include molybdenum (Mo).

[0052] The catalyst metal may be loaded in an amount of 0.01 wt % to 3 wt % based on the total weight of the catalyst. If the loaded amount of the catalyst metal is less than 0.01 wt %, it cannot be loaded itself and it is difficult to expect an improvement in catalytic activity. If it exceeds 3 wt %, agglomeration between the catalyst metals occurs and the catalytic activity may decrease.

[0053] The shape and / or size of the catalyst metal can be adjusted according to the environment of the heat treatment step of the production method described later. This will be described later.

[0054] The method for producing a catalyst according to the present invention comprises the following steps: a step of impregnating a catalyst metal precursor solution into a support body comprising a single crystal substance having a hexagonal crystal structure; a step of drying the impregnated product; and a step of heat-treating the dried product to obtain a catalyst having a catalyst metal supported on the support body. The method for producing the catalyst may include a configuration substantially repeating the aforementioned catalyst-related content, and the detailed description of the repeated part is omitted.

[0055] First, a catalyst metal precursor solution is impregnated on a support. In an exemplary embodiment, when the catalyst metal is ruthenium, the catalyst metal precursor may include RuCl3, RuCl3·xH2O, RuCl3·3H2O, [Ru(NH3)6]Cl2, Ru3(CO) 12 , C 16 H 22 O2Ru、C 18 H 26 Such as etc.

[0056] Next, the impregnated product may be dried. In an exemplary embodiment, the drying may be performed at 40° C. to 100° C. Furthermore, the impregnated product may be vacuum dried.

[0057] The dried product may be subjected to heat treatment to obtain a catalyst having a catalyst metal supported on the support. In an exemplary embodiment, the heat treatment may be performed at a temperature of 200 to 700° C. for 3 to 5 hours. If the temperature is lower than 200° C., the catalyst metal may not be fixed to the surface of the support, and if the temperature exceeds 700° C., agglomeration between the catalyst metals may occur, and the catalytic activity may decrease.

[0058] Furthermore, the heat treatment may be performed in an air environment, an inert gas environment or a vacuum environment. The inert gas environment may be an argon environment, a nitrogen environment or the like.

[0059] If the heat treatment is performed in an air environment, the catalyst metal can be formed into rod-shaped particles. The length of the catalyst metal in the rod shape can be 10 nm to 80 nm and the aspect ratio can be 1.2 to 20, but is not limited thereto. In this way, if the catalyst metal is formed into rod-shaped particles, the number of sites having high activity for the ammonia decomposition reaction increases.

[0060] If the heat treatment is performed in an inactive gas environment or a vacuum environment, the catalyst metal can be formed into particles of any one or more forms selected from the group consisting of hexagons, spheres, and semi-spheres. The diameter of the particles can be 2nm to 40nm, but is not limited to this. In this way, if the catalyst metal is formed into particles of any one or more forms selected from the group consisting of hexagons, spheres, and semi-spheres, a catalyst with a relatively high dispersion can be obtained. In addition, by heat treatment in an inactive gas environment or a vacuum environment, the catalyst metal can be epitaxially grown. Here, epitaxial growth refers to the growth of the catalyst metal along the skeleton of the hexagonal crystal structure of the support. By epitaxially growing the catalyst metal, a specific surface or site of the catalyst metal that helps to improve the ammonia decomposition activity can be grown.

[0061] Hereinafter, the present invention will be described in more detail by way of examples and experiments, but the present invention is not limited to the contents described below.

[0062] Example 1

[0063] Hexagonal boron nitride was prepared as a support. Ru3CO 12A mixture of tetrahydrofuran and ruthenium was impregnated into the support and dried at about 40 to 80° C. for about 12 hours. The dried product was heat-treated at 200 to 700° C. for about 3 hours in an air environment to obtain a catalyst. The catalyst was manufactured in a manner that contained 1% by weight of ruthenium.

[0064] Example 2

[0065] A catalyst was produced in the same manner as in Example 1 except that the dried product was heat-treated in an argon atmosphere as an inert gas.

[0066] Example 3

[0067] A catalyst was produced in the same manner as in Example 1 except that the dried product was heat-treated under a vacuum environment.

[0068] Comparative Example 1

[0069] A catalyst was produced by performing the same steps as in the above-described embodiment, except that silicon dioxide (SiO 2 ) was used as a support instead of hexagonal boron nitride and the amount of ruthenium supported was increased to 1.5% by weight.

[0070] Compared to Example 2

[0071] A catalyst was produced by performing the same steps as in the above-described embodiment except that Al 2 O 3 was used as a support instead of hexagonal boron nitride.

[0072] Experimental Example 1: XRD Analysis

[0073] The catalyst according to Example 1 was subjected to X-ray diffraction analysis. The results are as follows: Figure 1 Referring to this figure, peaks are observed for both hexagonal boron nitride and ruthenium, and it can be seen that ruthenium is normally supported on hexagonal boron nitride as a support.

[0074] Experimental Example 2: Determination of ammonia conversion rate with temperature

[0075] Ammonia dehydrogenation reaction was carried out using the catalysts according to Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and the conversion rate was measured.

[0076] First, 40 mg of each catalyst was filled into a packed bed reactor with a diameter of 3 / 8". The specific measurement conditions were a temperature of 350 to 450°C, a flow rate of 60,000 mL / g. cat .h GHSV (NH3), 2 hours of reduction time. The results are as follows Figure 2 shown.

[0077] refer to Figure 2 It is understood that in the case of Examples 1 and 2, compared with Comparative Examples 1 and 2, although the supported amount of the catalyst metal is the same or less, the ammonia conversion rate is higher.

[0078] Experimental Example 3: Morphology and size of catalyst metals depending on the heat treatment environment

[0079] TEM (Transmission electron microscope) analysis was performed on the catalysts according to Example 1, Example 2 and Example 3. The results are as follows: Figure 3a , Figure 3b and Figure 3c shown.

[0080] refer to Figure 3a It is known that when the heat treatment is performed in an air environment, the catalyst metal is formed into rod-shaped particles.

[0081] refer to Figure 3b It is found that when the heat treatment is performed in an inert gas atmosphere, the catalyst metal is formed into hexagonal, spherical, and hemispherical particles.

[0082] refer to Figure 3c It is known that when the heat treatment is performed in a vacuum environment, the catalyst metal is formed into spherical and hemispherical particles.

[0083] And, reference Figure 3b and Figure 3c It is known that when heat treatment is performed in an inert gas environment or a vacuum environment, the catalyst metal grows epitaxially along the support body.

[0084] Experimental Example 4: TOF (Turn over frequency) calculation

[0085] Based on the results of measuring the ammonia conversion in Experimental Example 2, the TOF of the catalyst according to the example was calculated at 450° C. The results are shown in Table 1 below.

[0086] [Table 1]

[0087]

[0088] 1) The catalyst metal and the loading amount are recorded on the left side of the slash ( / ), and the support is recorded on the right side. Referring to Table 1, it can be seen that the TOF of the catalyst according to the embodiment of the present invention is much higher than the TOF of the known ammonia dehydrogenation reaction catalyst. Therefore, it can be confirmed that the efficiency of the catalyst according to the present invention is very excellent.

[0089] The above is a description of the non-limiting and illustrative embodiments of the present invention, but the technical concept of the present invention is not limited to the drawings or the above description. For those with ordinary skills in the art, it is self-evident that various modifications can be made without departing from the technical concept of the present invention, and these modifications should also fall within the scope of the claims of the present invention.

Claims

1. A method for producing a catalyst, characterized in that: The steps include: A step of impregnating a catalyst metal precursor solution into a support including a single-crystalline substance of a hexagonal crystal structure to form an impregnated product; A step of drying the impregnated product; and The step of heat-treating the dried resultant at 200° C. to 700° C. for 3 to 5 hours in an air environment or a vacuum environment to obtain a catalyst having a catalyst metal supported on the support, wherein the single crystal material comprises at least one selected from the group consisting of hexagonal boron nitride (h-BN), boron nitride nanotubes (BNNTs), boron nitride nanoribbons (BNNRs) and boron nitride nanosheets, and The catalyst metal includes one or more selected from the group consisting of ruthenium (Ru), nickel (Ni), rhodium (Rh), iridium (Ir), cobalt (Co), iron (Fe), platinum (Pt), chromium (Cr), palladium (Pd) and copper (Cu).

2. The method for producing a catalyst according to claim 1, wherein: The catalyst metal is loaded in an amount of 0.1 wt % to 3 wt % based on the total weight of the catalyst.

3. The method for producing a catalyst according to claim 1, wherein: heat-treating the dried resultant in an air environment to form the catalyst metal into rod-shaped particles, The rod-shaped particles have a length of 10 nm to 80 nm and an aspect ratio of 1.2 to 20.

4. The method for producing a catalyst according to claim 1, wherein The dried product is heat-treated under a vacuum environment to form the catalyst metal into particles having any one or more shapes selected from the group consisting of spherical and hemispherical shapes, The diameter of the particles is 2 nm to 40 nm.